REVIEW of the monograph by E.I. Kobakhidze, V.Z. Dzidzishvili entitled “Essays on the history of the Georgian diaspora in Ossetia.” Vladikavkaz: SOIGSI VSC RAS, 2022. 260 p. - Sinanov, Boris Andreevic; Solov'eva, Lubov' Timofeevna (History, Archeology and Ethnography of the Caucasus, 2023)
The review of the monograph by E.I. Kobakhidze and V.Z. Dzidzishvili, titled “Essays on the history of the Georgian diaspora in Ossetia” (Vladikavkaz, 2022), critically examines the primary research findings of the team of authors. The review underscores the work’s relevance and high scientific merit. The authors conduct a comprehensive analysis of the Georgian diaspora’s formation and present status in North Ossetia within a broad chronological framework. The monograph emphasizes the early development of religious, cult, educational, and cultural aspects within the diaspora structure. Despite acknowledging challenging and at times dramatic periods in the relations of Georgia and Russia, the monograph convincingly illustrates the resilient adaptive capacities of the Georgian diaspora in Ossetia. Simultaneously, it highlights their capability to preserve their native culture and ethnic identity. The authors substantiate these claims by offering numerous narratives of the lives and biographies of prominent diaspora members, thereby demonstrating the significant involvement of Georgians in the socio-political and cultural life of North Ossetia. The comprehensive final conclusions of the study, grounded in an extensive source base and broad historiographical coverage, address the multifaceted nature of the tasks undertaken. The reviewers also commend the practical significance of the research, noting its potential as a noteworthy contribution to the field of Russian Caucasian studies. Furthermore, they recognize its value for federal and regional authorities responsible for managing issues related to interethnic relations.
Keywords: Georgian diaspora; migration processes; North Caucasus; Ossetia; Vladikavkaz; Alagir; Mozdok